Strengthening the Public Speaking Competence of PKK Women Through Assistance in Speech Text Preparation in Banjarsari Village, Banyuwangi Regency - Titik Indarti; Riki Nasrullah; Muhammad Bahruddin; Darni D; Djodjok Soepardjo; Urip Zaenal Fanani; Hespi Septiana (Yayasan Daarul Huda Kruengmane, 2026)
This community service activity was motivated by the important role of PKK women in various community forums, such as neighborhood meetings, posyandu activities, counseling sessions, village meetings, and ceremonial events. In this context, the ability to prepare speech texts and speak in public is an essential skill so that messages can be delivered clearly, systematically, politely, and convincingly. However, some participants still experienced difficulties in organizing speech structures, choosing communicative language, managing nervousness, controlling their voice, and building interaction with the audience. This activity aimed to improve the understanding and skills of PKK women in Banjarsari Village, Banyuwangi, in preparing speech texts and delivering them in a structured, clear, and confident manner. The activity was conducted on Monday, May 11, 2026, in Banjarsari Village, Banyuwangi, involving 25 participants. The implementation method used a participatory-educative approach through interactive lectures, discussions, speech text writing practice, speech simulations, direct feedback, and reflection. The results showed that participants experienced an improvement in understanding the structure of speech texts, especially in distinguishing the opening, body, and closing sections. Participants also became more capable of selecting themes relevant to PKK activities, using more communicative language, and delivering speeches with better articulation, tempo, intonation, eye contact, and gestures. In addition, participants’ responses to the activity indicated a high level of acceptance because the materials were considered relevant, easy to understand, and beneficial for their social roles. Therefore, assistance in speech text preparation and public speaking practice proved effective as a strategy for empowering public communication skills among PKK women and has the potential to be replicated in other women’s communities.